Implementasi Keselamatan dan Kesehatan Kerja (K3) Proyek-Proyek Transmisi dan Jaringan 150 kV (Studi Kasus: Pekerjaan Proyek Transmisi dan Jaringan Lopana-Teling) - Patkur, Hadi; Willar, Debby; Mandagi, Robert J. M. (Sam Ratulangi University, 2018)
The transmission and network project work from one substation to the next substation is thetransmission and electrical network work that will pass through some administrative areas so that: itwill have differences in the customs, culture, language, and geographical location of theadministrative region. This work are very vulnerable and potential to contain the risk of workaccidents, because the location of projects that tend to be in the middle of the forest, through valleys,mountains and yard residents, and the level of difficulty of the work itself that will lead tovulnerabilities in occupational safety and health such as erection work and withdrawal cable that mustwork on altitude of at least 30 meters. With such a risky background, all personnel involved in thiswork, whether directly or indirectly, should be aware of the importance of safety and health (OHS)implementation procedures that must be used at the time of this work process. All personnel should beaware and understand that at the time of the project location they must be obedient, ta'at, anddiscipline to always comply and implement the procedures of Occupational Safety and Health (OSH).This study is limited to the implementation of occupational safety and health (OHS)procedures on the 150 kV Transmission and Network project from Lopana to Teling located in SouthMinahasa, Minahasa Induk and Manado.The aims of this study was to develop a safety and health (OSH) implementation procedure tomotivate employees / workers successfully and successfully to be used or applied to transmission andnetwork project work. The method used is a survey with correlation approach, to reveal the real stateof things experienced by workers.Based on the results of the research and discussion above, it can be concluded that thevariables of OSH (X1) equipment, OSH (X2) training, OSH (X3) discipline, and companymanagement (X4) simultaneously affect the implementation of OSH on transmission and networkproject work of 80 , 7% and the remaining 19.3% are other variables not included in this research,where the effect of OSH equipment on OSH implementation is (0.563) 2 = 31,7%. The effect of OSHtraining on OSH implementation is (0.632) 2 = 39.9%. The magnitude of the effect of OSH disciplineon the implementation of OSH is (0.584) 2 = 34.1%. The magnitude of the effect of corporatemanagement on the implementation of OSH is (0.339) 2 = 11.5%.Â Keywords: occupational safety and health, work accident, transmission and network project.